Severe pneumococcal disease and temporary splenic dysfunction. Issue 857 (March 1997) - Pelly, M. D.; Huo, Z.; Henderson, D. C.; Soni, N.
Abstract : We report a patient presenting with pneumonia in whom temporary splenic dysfunction was diagnosed by counting pitted red blood cells. This under-recognised condition caused a transient immunosuppression which may have had serious implications for our patient's recovery.